A study on the tip tracking control of a single flexible beam - Castillo-Berrio, Claudia F.; Engin, Seref N.; Feliu-Batlle, Vicente (SAGE PUBLICATIONS LTD, 2016)
This sequential paper aims to present studies on modelling and tip tracking control of a flexible single beam. It first outlines the flexible-beam robotic mechanism that was designed and built to be used for the force and torque sensory information-based modelling and control. It then details the vibration suppression controller strategy that is applied to this robotic system. The controller is designed with respect to a simple lumped model describing the dynamics of the system. Here the dynamics of the closed-loop controlled motor is inverted in order to obtain a system with unity dynamics. Further, the flexible-beam dynamics is input state linearized. Finally, a simple external feedback control, which is based on the measurements of beam deflections using a force and torque sensor, is implemented. The complete experimental setup was positioned by two servo-motors controlled by a proportional-integral-derivative controller for each axis. The proposed controllers allow the flexible beam to move continuously in a precise manner, so that it could be treated as an accurate positioning sensor. Simulation and experimental results provided at the end illustrate that the controllers designed and implemented produce a satisfactory control performance and adequate robustness to model uncertainties and system nonlinearities.
Keywords: Motion control; flexible beam; vibration suppression; force and torque sensor; state linearization; proportional-integral-derivative control; FEEDBACK-CONTROL; MANIPULATORS; ROBOT; MODEL; ARMS; Automation & Control Systems; Instruments & Instrumentation